Use of laryngeal mask airway for non-endotracheal intubated anesthesia for patients with pectus excavatum undergoing thoracoscopic Nuss procedure - Du, Xiaojun; Mao, Songsong; Cui, Jianxiu; Ma, Jue; Zhang, Guangyan; Zheng, Yong; Zhou, Haiyu; Xie, Liang; Zhang, Dongkun; Shi, Ruiqing; Chen, Gang (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: The aim of the present study was to determine the safety and feasibility of the use of laryngeal mask airway (LMA) for non-endotracheal intubated anesthesia for patients with pectus excavatum (PE) undergoing thoracoscopic Nuss procedure. Methods: Between July 2015 and December 2015, 30 selected patients with PE were planned to undergo a thoracoscopic Nuss procedure using LMA for non-endotracheal intubated anesthesia in the Guangdong General Hospital. The clinical data were analyzed to evaluate the safety and feasibility of this technique. Results: Of the 30 selected patients, two were female, the mean age was 16.04±5.09 years and the average Haller index was 3.37±0.88. A total of 27 cases (90%) succeeded at the first attempt, one patient required conversion to an endotracheal tube (ETT) because of continuous air leak. The peripheral O2 saturation (SpO2), end-tidal carbon dioxide (EtCO2) values, heart rate (HR), and mean arterial blood pressure (MAP) remained stable throughout the procedure in all cases. All of the 30 patients were successfully corrected without requiring conversion to an open surgery. Two patients experienced postoperative nausea and one reported a sore throat. Neither gastro-esophageal reflux nor in-hospital mortality occurred. Conclusions: The use of LMA for non-endotracheal intubated anesthesia for selected patients with PE undergoing thoracoscopic Nuss procedure is clinically safe and technically feasible.